Dampak Media Sosial terhadap Dekadensi Moral di Kalangan Generasi Muda : Solusi Berbasis Nilai-Nilai Pancasila - Keisya Rahma Ayu; Muhammad Najwan; Ahmad Aurelio Gulam Ranaya; Herli Antoni (International Forum of Researchers and Lecturers, 2024)
Currently, social media has become an important part of the lives of the younger generation. On one hand, social media offers great benefits such as access to information, social networking, and creativity. However, irresponsible use can trigger negative impacts, one of which is moral decadence, especially among the younger generation. This research aims to analyze the impact of social media on the moral decadence of the younger generation and to design solutions based on Pancasila values. The method used is a literature review, analyzing information from various relevant academic sources. The research results show that social media, although beneficial, contributes to various moral issues, such as the increase in online bullying, the use of inappropriate language, becoming individualistic/antisocial, and engaging in cybercrime. As a solution, the values of Pancasila are implemented through spiritual education, digital campaigns that instill empathy and solidarity, promotion of tolerance and unity, as well as the enhancement of digital literacy. This research concludes that the implementation of Pancasila values can be a relevant and solution-oriented approach to addressing the moral decadence of the younger generation in the digital era.